2009
DOI: 10.1007/s12010-009-8836-0
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity Affects Growth of Escherichia coli and Recombinant β-d-Glucuronidase Production

Abstract: Effects of simulated microgravity (SMG) on bacteria have been studied in various aspects. However, few reports are available about production of recombinant protein expressed by bacteria in SMG. In this study growth of E. coli BL21 (DE3) cells transformed with pET-28a (+)-pgus in double-axis clinostat that could model low shear SMG environment and the recombinant beta-D-glucuronidase (PGUS) expression have been investigated. Results showed that the cell dry weights in SMG were 16.47%, 38.06%, and 28.79% more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…29 RPMs are commercially available by Mitsubishi Heavy Industries (Kobe, Japan) and Dutch Space (Leiden, The Netherlands), while various academic groups developed similar systems of 3D clinostats and RPMs. [35][36][37][38][39][40] Rotating wall vessel…”
Section: Random-positioning Machinementioning
confidence: 99%
“…29 RPMs are commercially available by Mitsubishi Heavy Industries (Kobe, Japan) and Dutch Space (Leiden, The Netherlands), while various academic groups developed similar systems of 3D clinostats and RPMs. [35][36][37][38][39][40] Rotating wall vessel…”
Section: Random-positioning Machinementioning
confidence: 99%
“…Changes in cellular functions include cell clumping, shortened lag phase and prolonged exponential phase in the gene expression, and protein folding to alter the productivities of the secondary metabolites in bacteria (Escherichia coli, Pseudomonas aeruginosa) and yeast (S. cerevisiae) (Benoit et al 2006;Baker et al 2004;Crabbé et al 2011;Sheehan et al 2007). Only a few studies have shown that microgravity can impact the heterologous proteins production, such as enhanced expression of the recombinant β-glucuronidase in E. coli, and β-galactosidase and glycodelin in human cells (Xiang et al 2010;Stephen 2007). In contrast, some other studies indicated that SMG could not always promote protein expression (Boyle et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…PGUS from Penicillium purpurogenum Li-3 screened in our previous work [17] can directly biosynthesize glycyrrhetinic acid monoglucuronide (GAMG) from glycyrrhizin (GL) (Fig. 2) [17,18]. GAMG is useful in clinical treatment of inflammatory diseases and is safer, more effective, and absorbable than GL [19].…”
Section: Rotationmentioning
confidence: 99%